Empowering Medan MSMEs through digital marketing training - Ahmad Afandi; Muhammad Arifin Lubis; Isra Hayati (Community Empowerment, 2023)
This article examines the implementation of community service programs aimed at improving the digital marketing capabilities of Micro, Small and Medium Enterprises (MSMEs) in Medan City. Focusing on collaboration with Lazismu Kota Medan, this study uses a three-stage approach: partner problem identification, training implementation and evaluation. Through meetings and surveys, the service team determines the training needs of MSMEs, which cover important aspects of digital marketing. The training was held at the Muhammadiyah Da'wah Building with interactive lecture methods, Kahoot application-based quizzes, and group discussions. Evaluation of the effectiveness of the training was carried out through pre-test and post-test, resulting in a significant increase in participants' digital marketing understanding. These results show that digital marketing training is effective in increasing the ability and confidence of MSMEs in digital marketing, providing important implications for the development of MSMEs and the local economy of Medan City.